2012
DOI: 10.1021/es2042383
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Isotope Fractionation During Reduction of Cr(VI) Under Saturated Flow Conditions

Abstract: Chromium isotopes are potentially useful indicators of Cr(VI) reduction reactions in groundwater flow systems; however, the influence of transport on Cr isotope fractionation has not been fully examined. Laboratory batch and column experiments were conducted to evaluate isotopic fractionation of Cr during Cr(VI) reduction under both static and controlled flow conditions. Organic carbon was used to reduce Cr(VI) in simulated groundwater containing 20 mg L(-1) Cr(VI) in both batch and column experiments. Isotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…However, it is also important to evaluate more complex systems, such as the experiment conducted in this study, to extend the understanding of Zn isotope behaviour to a system where multiple geochemical processes may be involved. In addition, it is essential to consider the effect of saturated flow conditions, as flow dynamics can influence the degree of isotope fractionation (Jamieson-Hanes et al, 2012;Jamieson-Hanes et al, 2015). Results from this study demonstrate that the application of Zn isotope ratio measurements, combined with XAS and aqueous geochemical measurements, can provide valuable insight into the complex geochemical systems encountered in field studies.…”
Section: Implications For Field Studiesmentioning
confidence: 90%
“…However, it is also important to evaluate more complex systems, such as the experiment conducted in this study, to extend the understanding of Zn isotope behaviour to a system where multiple geochemical processes may be involved. In addition, it is essential to consider the effect of saturated flow conditions, as flow dynamics can influence the degree of isotope fractionation (Jamieson-Hanes et al, 2012;Jamieson-Hanes et al, 2015). Results from this study demonstrate that the application of Zn isotope ratio measurements, combined with XAS and aqueous geochemical measurements, can provide valuable insight into the complex geochemical systems encountered in field studies.…”
Section: Implications For Field Studiesmentioning
confidence: 90%
“…Laboratory experiments have demonstrated that the degree of fractionation is dependent on the mechanism of removal and the electron donor, as summarized in Table 1. Materials used to induce reduction in these experiments include ferrous iron, both as Fe(II) aq and in the form of Fe(II)-bearing minerals (Ellis et al, 2002;Berna et al, 2010;Døssing et al, 2011;Kitchen et al, 2012;Basu and Johnson, 2012), organic carbon (Kitchen et al, 2012;Jamieson-Hanes, Gibson et al, 2012), Cr-reducing bacteria (Sikora et al, 2008;Han et al, 2012), and hydrogen peroxide (Zink et al, 2010). A large range of values has been reported for Cr isotope fractionation during reduction of Cr(VI) ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Enriched  53 Cr values have also been observed in field samples collected at both anthropogenically and naturally contaminated sites, but system heterogeneities and complex flow regimes have posed considerable challenges for data interpretation (Ellis et al, 2002;Izbicki et al, 2008;Berna et al, 2010;Raddatz et al, 2011;Villalobos-Aragón et al, 2012;Wanner, Eggenberger, Kurz, et al, 2012;Izbicki et al, 2012). Jamieson-Hanes, Gibson, et al (2012) explored the potential influence of transport by comparing Cr(VI) reduction by organic carbon in a batch and a column experiment. A significant difference was observed in the isotope behaviour under static and saturated flow conditions, and was attributed to the presence of multiple Cr removal mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equilibrium fractionations between Cr (VI) and Cr (III) were estimated by Schauble [171], who predicted Cr isotope fractionations of >1‰ between Cr species with different oxidation states. Ellis et al [172], Sikora et al [173], Berna et al [174], Zink et al [175], Dossing et al [176], Basu and Johnson [177], Han et al [178], Jamieson-Hanes et al [179], and Kitchen et al [180] studied the fractionation of Cr isotopes in a series of Cr(VI) reduction experiments. The results showed a general trend of accumulating heavier Cr isotopes in the unreacted Cr(VI) species and an accumulation of the lighter ones in the produced Cr(III), whereas Cr(III) did not undergo rapid isotopic exchange during Cr(III) oxidation runs [175].…”
Section: Chromium Isotopesmentioning
confidence: 99%